2006
DOI: 10.1002/pmic.200500844
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic signature of human embryonic stem cells

Abstract: Human embryonic stem cells (hESC) represent a population of undifferentiated pluripotent cells with both self-renewal and multilineage differentiation characteristics. Proteomics provides a powerful approach for studying the characteristics of hESC and discovering molecular markers. We have analyzed proteome profiles of three hESC lines using 2-DE and MALDI TOF-TOF. Out of 844 spots analyzed with MALDI TOF-TOF, 685 proteins were identified of which 60 proteins were classified as the most abundant proteins on 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 34 publications
(27 reference statements)
3
65
0
4
Order By: Relevance
“…In addition, they were able to verify the presence of these newly identified factors in 3 undifferentiated hESC lines: EES2, HUES-1 and NL-hESC-03 [18]. The second study used conventional 2-D gels to compare the undifferentiated proteomes of the Royan H2, H3 and H5 hESC lines [19]. In the present study, we hypothesized that the H1 and HES2 lines have distinct preferences to become chamber-specific heart cells, and that their different cardiogenic potentials are predetermined at the pluripotent stage due to discrete differences in their proteomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they were able to verify the presence of these newly identified factors in 3 undifferentiated hESC lines: EES2, HUES-1 and NL-hESC-03 [18]. The second study used conventional 2-D gels to compare the undifferentiated proteomes of the Royan H2, H3 and H5 hESC lines [19]. In the present study, we hypothesized that the H1 and HES2 lines have distinct preferences to become chamber-specific heart cells, and that their different cardiogenic potentials are predetermined at the pluripotent stage due to discrete differences in their proteomes.…”
Section: Introductionmentioning
confidence: 99%
“…Careful analysis on all isoforms of a given protein is very important because many of the interesting regulatory steps, especially those involved in cell proliferation, migration and differentiation, count on protein PTM more than they do on protein expression levels (Levchenko, 2005). Baharvand et al (2006b) identified a large number of proteins involved in protein synthesis, processing, and trafficking. Such finding suggests that hESCs are able to maintain the undifferentiated state until signals of lineage determination is received, upon which these cells quickly change phenotype and produce necessary proteins.…”
Section: Human Embryonic Stem Cellsmentioning
confidence: 99%
“…Also, Baharvand et al (2006b) have applied 2-DE and MALDI TOF-TOF MS/MS (4700 Proteomics Analyzer, Applied Biosystems) to profile global map of proteome expressed in hESC. Cell line samples were analyzed in triplicate using 2-DE and 1,250 ± 150 spots were detected.…”
Section: Human Embryonic Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations